Gerakan protes petani Unra : suatu studi sejarah sosial di pedalasan agraris Sulawesi Selatan : laporan penelitian - Limbugau, Daud (Lembaga Penelitian, Universitas Hasanuddin, 1991)
Unra farmer movement during the Japanese military occupation, 1943 in Bone, Sulawesi Utara Province; research report.